Pengembangan E-LKPD Berbasis Predict-Observe-Explain (POE) Menggunakan Liveworksheets pada Materi Kesetimbangan Ion dan pH Larutan Penyangga - Sarmila Eka Putri; Abdullah Abdullah; Sri Wilda Albeta (Universitas Pendidikan Mandalika Mataram, 2022)
This research was conducted at the Chemical Education Study Program, Faculty of Teacher Training and Education (FKIP) Riau University, Pekanbaru in the even semester of 2021/2022 with trials conducted at SMAN 3 Tualang and SMAN 6 Pekanbaru. This study aims to produce POE-based E-LKPD using Liveworksheets on the subject of ionic solutions and pH of buffer solutions. Using the Plomp development model, this study was planned as part of the R&D process. Validation sheet and user feedback survey used for data collection. Validation was carried out by four independent validators, showing the percentage of valid categories of 98.21%, 100%, 96.87%, 95.83%, and 93.05% for incorrect, POE model features, language, presentation, and visuals. 3 students participated in an individual trial, in which data on the amount of time and scores obtained from using the E-LKPD, as well as students' ideas and feedback, were collected. The average percentage of teacher evaluation of E-LKPD is 93.98%, and the percentage of student evaluation is 89.34%; This finding shows that the E-LKPD created is in accordance with the education setting.